Income Taxation from Activity Provision in the Field of Medical/Dental Care - Lucian CERNUȘCA (CECCAR Business Review)

(untitled)
Activity provision in the field of medical/dental care is classified from a fiscal point of view as income from independent activities, and the doctors who carry them out are required to become authorized in accordance with the legal provisions in force and to fulfill their declaration and payment obligations. These tax obligations are reported in the single tax return (form 212). The income tax that doctors who practice liberal professions within their own medical office must pay into the state budget is established by reference to the annual net income and is actually determined based on accounting data. The social health insurance contribution is calculated on the net income obtained, and the calculation base cannot be less than six gross minimum wages nor greater than 60 gross minimum wages. The social insurance contribution is determined by taxpayers by applying a 25% rate to the calculation base, if the annual net income exceeds 12 gross minimum wages.